ANALYSIS OF THE ROLE OF ENVIRONMENTAL REGULATIONS IN ACHIEVING SUSTAINABILITY PERFORMANCE - Syntia Ratna Dewi; Andi Basru Wawo; Nur Asni (RADJA PUBLIKA, 2026)
The purpose of this study is to investigate how environmental regulation in enhancing corporate sustainability performance. Using a qualitative approach through literature review, this research explores how environmental policies, sustainability reporting, and green accounting practices contribute to corporate accountability and long-term value creation. The findings indicate that rules suc as Indonesia’s POJK No. 51/POJK.03/2017 effectively drive greater transparency and ecological responsibility among businesses. Furthermore, governance quality, managerial capacity, and organizational structure are determined to be essential for the effective execution of these regulations. This research provides practical insights for policymakers and scholars, and highlights future research directions in environmental audit digitalization and sustainability innovation across industries